Evaluation of recurrent selection based on roguing, S1 progeny test and S1 line breeding in a sweet corn variety - Yap, T. C.; Tan, S. T. (Faculty of Agriculture, University of Malaya, 1974)
Three types of recurrent selection were carried out in the Chinta variety of sweet corn. The results mdrcateo that: (I) S, line breeding was the most effective; (ii] simple recurrent selection based on roguing undesirable plants in a bulked population before anthesis was second; (iii) recurrent selection based on yield performance of S, progeny test was third. Selection for yield and caused some effect on other agronomic characters.